2016
DOI: 10.4067/s0717-95022016000400036
|View full text |Cite
|
Sign up to set email alerts
|

Variable Morphology of the Hyoid Bone in Anatolian Population: Clinical Implications - A Cadaveric Study

Abstract: SUMMARY:The variations of the hyoid bone has a great significance for surgical procedures of neck region, and in forensic medicine for evidence of strangulation or hanging, which causes fractures. The aim of this study was to investigate the morphological and morphometrical variations of the hyoid bone in Anatolian population. A total of 60 adult larynx specimens (46 male, 14 female) were dissected to identify morphological and morphometrical variations of hyoid. The infrahyoid muscles and thyrohyoid membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…For major transverse axis, that is, the distance between interior contours of greater horns (parameter "c") the mean value is 37.41 ± 6.79 in males and 35.69 ± 6.70 in females, which is more than the mean values of other studies. 1,[8][9][10] For the length of hyoid body (parameter "d") the mean value is 21.09 ± 3.21 in males and 19.18 ± 2.52 in females, which is similar to the studies done by Ramagalla 9 in 2014 and Santhi Priya et al 1 in 2015; it is very less than the mean values of other studies done by Kopuz 8 and Harjeeth and Jit. 10 For total left hyoid length (parameter "g") and total right hyoid length (parameter "h") the mean values of the present study is very less than the mean values of study done by Kopuz et al 8 In the present study, it is observed that the male hyoid bone values are more (10.09 ± 1.40) when compared with female (9.55 ± 1.03) regarding the distance between the upper and lower margins of the body in the middle (height).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…For major transverse axis, that is, the distance between interior contours of greater horns (parameter "c") the mean value is 37.41 ± 6.79 in males and 35.69 ± 6.70 in females, which is more than the mean values of other studies. 1,[8][9][10] For the length of hyoid body (parameter "d") the mean value is 21.09 ± 3.21 in males and 19.18 ± 2.52 in females, which is similar to the studies done by Ramagalla 9 in 2014 and Santhi Priya et al 1 in 2015; it is very less than the mean values of other studies done by Kopuz 8 and Harjeeth and Jit. 10 For total left hyoid length (parameter "g") and total right hyoid length (parameter "h") the mean values of the present study is very less than the mean values of study done by Kopuz et al 8 In the present study, it is observed that the male hyoid bone values are more (10.09 ± 1.40) when compared with female (9.55 ± 1.03) regarding the distance between the upper and lower margins of the body in the middle (height).…”
Section: Discussionsupporting
confidence: 68%
“…Santhipriya et al 1 Kopuz et al 8 Ramagalla et al 9 Harjeeth et al 10 Present study Abbreviations: M, male; F, female. Note: Parameters 1-9 are in millimeters and parameter 10 is in grams.…”
Section: Conflict Of Interestmentioning
confidence: 74%
See 2 more Smart Citations
“…[16][17][18] In more comprehensive classification studies, the hyoid bone has been divided into 5 types based on its symmetry, isometry, width, and two-dimensional measurements. 19 In addition to this classification, Kopuz & Ortug 20 added Type-HK as another variation.…”
mentioning
confidence: 99%